2017
DOI: 10.1590/0100-69912017003001
|View full text |Cite
|
Sign up to set email alerts
|

Preditores de mortalidade em pacientes com fratura de pelve por trauma contuso

Abstract: RESUMO Objetivo: analisar a associação de mortalidade com variáveis sociodemográficas, clínicas, lesões e complicações em pacientes com trauma de pelve decorrente de trauma contuso. Métodos: estudo retrospectivo e observacional com dados de registro de trauma obtidos durante cinco anos. O óbito foi a variável de estratificação das análises. Para verificar se as variáveis de interesse tinham associação com o óbito, foi realizado o teste t de Student e teste do Qui-quadrado (ou Fisher) e Wilcoxon-Mann Whitney.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(16 reference statements)
0
5
0
1
Order By: Relevance
“…Older patients tend to have a worse prognosis, even in mechanically stable fractures 22 . Correa et al 23 reported that a risk of death in patients older than 50 years 28.3 times higher than in patients younger than 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients tend to have a worse prognosis, even in mechanically stable fractures 22 . Correa et al 23 reported that a risk of death in patients older than 50 years 28.3 times higher than in patients younger than 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…High-energy trauma patients pose a particular challenge for clinicians, because of elevated risk for potentially fatal complications, [4][5][6][7] and routinely undergo emergency WBCT upon admission to hospital. Besides injury assessment, the CT scans can effortlessly be used for BCA, which is on its way to clinical routine practice to enhance patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying variables and risk factors that lead to complications or death after trauma remains a focus of research 2,3 . High‐energy trauma results from a high‐impact force, such as motor vehicle accidents, falls from significant heights, or blast injuries, and poses a particular challenge for clinicians, as these trauma mechanisms are associated with potentially fatal complications, such as injuries to multiple body regions and severe bleeding 4–7 . Quick and systematic assessment of all injuries and individual risk factors is crucial to initiate adequate treatment 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A maior incidência de coagulopatia verificada neste estudo pode ter tido influência da utilização da tromboelastometria em alguns casos em que este recurso estava disponível, método este que possui maior acurácia para detectar distúrbios na coagulação (60) . Em estudo retrospectivo que analisou preditores de mortalidade em pacientes com fratura de pelve, Corrêa et al (52) Quando consideramos todos os pacientes com alguma fratura de pelve, as lesões arteriais estão presentes somente em 10% a 20%, e a arteriografia é indicada em apenas 3 a 10% dos casos (76,105,(107)(108)(109) .…”
Section: Segmentos Corpóreosunclassified